Live Attenuated Influenza Vaccines engineered to express the nucleoprotein of a recent isolate stimulate human influenza CD8+ T cells more relevant to current infections - D. Korenkov; T. H. O. Nguyen; I. Isakova-Sivak; T. Smolonogina; L. E. Brown; K. Kedzierska; L. Rudenko (Taylor & Francis Group, 2018)
Live attenuated influenza vaccines (LAIV) induce CD8+ T lymphocyte responses that play an important role in killing virus-infected cells. Despite the relative conservation of internal influenza A proteins, the epitopes recognized by T cells can undergo drift under immune pressure. The internal proteins of Russian LAIVs are derived from the master donor virus A/Leningrad/134/17/57 (Len/17) isolated 60 years ago and as such, some CD8+ T cell epitopes may vary between the vaccine and circulating wild-type strains. To partially overcome this issue, the nucleoprotein (NP) gene of wild-type virus can be incorporated into LAIV reassortant virus, along with the HA and NA genes. The present study compares the human CD8+ T cell memory responses to H3N2 LAIVs with the Len/17 or the wild-type NP using an in vitro model.